2008
DOI: 10.3747/co.2008.200
|View full text |Cite
|
Sign up to set email alerts
|

Health Management Program: Factors Influencing Completion of Therapy with High-Dose Interferon Alfa-2b for High-Risk Melanoma

Abstract: The goal of the 1-year observational, multicentre, open-label study reported here was to identify factors influencing adherence to high-dose interferon alfa-2b adjuvant therapy in patients at high risk of recurrence following surgical excision of malignant melanoma. The study was carried out in 23 tertiarycare centres across Canada.The 225 patients enrolled in the study all had malignant melanoma that was surgically excised and that required adjuvant treatment with interferon alfa-2b. Of these patients, 64% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…This observation suggests that dose adjustment is particularly relevant for treatment tolerance and should be considered as soon as side effects appear. This has also been observed elsewhere 1 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This observation suggests that dose adjustment is particularly relevant for treatment tolerance and should be considered as soon as side effects appear. This has also been observed elsewhere 1 .…”
Section: Discussionsupporting
confidence: 87%
“…In this series, 83% of the patients completed the full 52-week expected treatment 15 ; other larger studies reported figures similar to those reported here. A Canadian study with 225 patients showed that 41% completed the full therapy 1 . In the present study, a Cox regression analysis showed that age was a strong predictive factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations